CONGENITAL rNTERNAL HYDROCEPHALUS IN A NEW BORN COW CALF - JANA, DEBASIS; GHOSH, MOUSUMI (The Indian Journal of Animal Reproduction, 2023)
A case of congenital internal hydrocephalus in a new born indigenous cow calf and its successfultherapeutic management has been reported.
Keywords: Hydrocephalus; Congenital calf; Treatment